ЭКСПЕРИМЕНТАЛЬНОЕ ОБОСНОВАНИЕ ВЛИЯНИЯ Минеральной воды СКВАЖИНЫ № 1656 г. СТАРОБЕЛЬСЬК НА СТРУКТУРНО-ФУНКЦИОНАЛЬНЫЕ НАРУШЕНИЯ ХРЯЩЕЙ ПРИ ВОСПАЛИТЕЛЬНО-ДИСТРОФИЧЕСКИХ ПОРАЖЕНИЯХ = EXPERIMENTAL SUBSTANTIATION INFLUENCE OF MINERAL WATER WELL NUMBER 1656 STAROBILSK ON STRUCTURALLY FUNCTIONAL DISORDERS OF CARTILAGE IN INFLAMMATORY-DYSTROPHIC LESIONS - B. A. Nasibullin; E. I. Platonova (Kazimierz Wielki University, 2016)
Nasibullin B. A., Platonova E. I. ЭКСПЕРИМЕНТАЛЬНОЕ ОБОСНОВАНИЕ ВЛИЯНИЯ Минеральной воды СКВАЖИНЫ № 1656 г. СТАРОБЕЛЬСЬК НА СТРУКТУРНО-ФУНКЦИОНАЛЬНЫЕ НАРУШЕНИЯ ХРЯЩЕЙ ПРИ ВОСПАЛИТЕЛЬНО-ДИСТРОФИЧЕСКИХ ПОРАЖЕНИЯХ = EXPERIMENTAL SUBSTANTIATION Influence of mineral water well number 1656 Starobilsk on structurally functional disorders of cartilage In inflammatory-dystrophic lesions. Journal of Education, Health and Sport. 2016;6(9):674-681. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159063 http://ojs.ukw.edu.pl/index.php/johs/article/view/3891       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016.       ЭКСПЕРИМЕНТАЛЬНОЕ ОБОСНОВАНИЕ ВЛИЯНИЯ Минеральной воды СКВАЖИНЫ № 1656 г. СТАРОБЕЛЬСЬК НА СТРУКТУРНО-ФУНКЦИОНАЛЬНЫЕ НАРУШЕНИЯ ХРЯЩЕЙ ПРИ ВОСПАЛИТЕЛЬНО-ДИСТРОФИЧЕСКИХ ПОРАЖЕНИЯХ   Б. А. Насибуллин, Е. И. Платонова   ГУ «Украинский НИИ медицинской реабилитации и курортологии МЗ Украины»               Авторы, при проведении экспериментальных исследований на 80 белых крысах-самцах, выявили, что развитие  экспериментального дексаметазонового артрита сопровождается воспалительными и дистрофически-дегенеративными изменениями в хряще и окружающих тканях поврежденного сустава. Проведение цикла аппликаций МВ СКВ. № 1656 г. Старобельск на поврежденный сустав снижает интенсивность воспалительных и дегенеративных изменений в хряще, а через 15 дней опыта (6 аппликаций) обеспечивает восстановление структурно-функциональной организации хряща. Авторы полагают возможным использовать данную МВ при аналогичной патологии в других хрящах.             Ключевые слова: хрящ, артроз, минеральные воды.                      EXPERIMENTAL SUBSTANTIATION Influence of mineral water well number 1656 Starobilsk on structurally functional disorders of cartilage In inflammatory-dystrophic lesions   B. A. Nasibullin, E. I. Platonova   The Ukrainian scientific and research institute of medical rehabilitation and balneology of the Ministry of health of Ukraine   Authors, during the experimental studies on 80 white male rats, revealed that the development of experimental arthritis dexamethasone suppression accompanied by inflammatory and dystrophic-degenerative changes in the cartilage and surrounding tissues of the affected joint. Carrying loop applications MW SLE. Number 1656 Starobelsk on the damaged joint reduces the intensity of the inflammatory and degenerative changes in the cartilage, and after 15 days of the experiment (6 applications) ensures the recovery of structural and functional organization of the cartilage. The authors believe it possible to use this MB at a similar disease in other cartilage. Keywords: cartilage, osteoarthritis, mineral water.